Moderating effect of audit quality: the case of political connection, executive compensation and tax aggressiveness - Sihono, Agus; Munandar, Agus (Jurnal Ekonomi Modernisasi, 2023)
The study examines the moderating effect of audit quality on relationship between political connection, executive compensation on tax aggressive. The secondary data used for this study in the form of financial statements of 56 financial sector firms listed on Indonesian stock exchange from 2018 to 2021. Moderated Regression Analysis used for analyzed data. Result indicate, that political connection positively affected tax aggressive. These result support the view of grabbing hand theory, where a bureaucrat who occupies a position in the company will be controlled by the corporation because they get welfare. Furthermore, we find that executive compensation negatively affected tax aggressive. The result of moderation analysis show that audit quality can weaken the relationship of executive compensation on tax aggressive. These findings of this research suggest that audit quality is an effective corporate governance mechanism, thereby protecting users against the opportunism and fraud by managers. This show that corporate governance is able to mitigating information asymmetry that exist in the relation between agent and principals.